Literary Traditions: English in Malaysia and Singapore (Column 4) - Quayum, Mohammad Abdul (The Daily Star, Bangladesh, 2014)
It is true that English writings have made phenomenal advances in many of the postcolonial societies in the last fifty odd years, so much so that Salman Rushdie made the controversial claim that English writing has been more prolific in India in the post-independence period than literature in its sixteen “official languages” and that “'Indo-Anglian' literature represents perhaps the most valuable contribution India has yet made to the world of books.” Rushdie's claim might sound a bit audacious, but certainly countries like India, South Africa or even neighbouring Singapore can profess to be literary centres so far as English writing is concerned because of the sheer volume and quality of literature they have produced in the language. But can Malaysia be included in this league? Does it have a body of writing substantial and challenging enough to make it into a literary hub in English? The answer is not so clear because Malaysia has produced an oeuvre of writings in the language and yet the growth of literary activity in the medium has not been steady, substantial and continuous as compared to other countries. This is of course not to blame the individual writers because Malaysia has produced some very good writers in English, who are comparable to the best writers in Singapore for example, but the socio-political-cultural circumstances have dogged the English literary scene, including the careers of its most established writers, from the beginning.